(untitled) (Journal of the College of Basic Education, 2022)
The research dealt with the study of wind erosion in Al-Qadisiyah Governorate through the use of mathematical equations and statistical methods and their application to the study data. The analysis of the elements and some climatic phenomena revealed fluctuations in them and their reflection on the dry climate prevailing in the region, which leads to high values of wind erosion and its reflection on the movement of sand dunes and their different distribution in the region. which are distributed differently in the region. There is a direct relationship between wind erosion and the expansion of areas affected by sand dunes through a comparative study between the area of sand dunes in 2000, and it amounted to (453 km2), but in 2018 it amounted to (804 km2), As for the statistical model for the region, it showed a positive relationship, The value of R2 reached (84%) between the variables within the model (wind speed, evaporation - transpiration, drought) and their impact on wind erosion and this is reflected on the movement of sand dunes. As well as the relationship between wind erosion and the area of agricultural land was positive (strong) and amounted to (0.79), and the interpretation coefficient (R2) amounted to (62%).